2010
DOI: 10.1111/j.1365-2958.2010.07488.x
|View full text |Cite
|
Sign up to set email alerts
|

The co-dependence of BxpB/ExsFA and BclA for proper incorporation into the exosporium of Bacillus anthracis

Abstract: SummaryThe outermost layer of the Bacillus anthracis spore consists of an exosporium comprised of two distinct layers, an outer hair-like nap layer and an internal basal layer. The hair-like nap is primarily comprised of the glycosylated collagen-like protein BclA. BclA is found in a trimeric form in close association with many other exosporium proteins in high-molecular weight complexes. We previously had characterized an N-terminal sequence of BclA that is sufficient for incorporation into the exosporium. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 39 publications
7
78
0
Order By: Relevance
“…Therefore, my colleagues and I have proposed a model whereby BxpB is delivered to the spore by virtue of forming a complex with BclA and possibly, to a lesser extent, with other exosporium-targeting motif sequences (58). In keeping with this, we observed a reduction in the amount of BxpB extractable from spores of a BclA-negative strain, a finding similar to that observed by others (65,66,68). However, this model is disputed by Rodenburg et al (39), based on their analysis of B. anthracis spore structure by high-resolution electron microscopy.…”
Section: Assembly Of the Exosporiumsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, my colleagues and I have proposed a model whereby BxpB is delivered to the spore by virtue of forming a complex with BclA and possibly, to a lesser extent, with other exosporium-targeting motif sequences (58). In keeping with this, we observed a reduction in the amount of BxpB extractable from spores of a BclA-negative strain, a finding similar to that observed by others (65,66,68). However, this model is disputed by Rodenburg et al (39), based on their analysis of B. anthracis spore structure by high-resolution electron microscopy.…”
Section: Assembly Of the Exosporiumsupporting
confidence: 90%
“…An N-terminal targeting sequence of BclA and certain other collagen-like proteins is responsible for positioning these proteins at the site of the developing exosporium (57,58,(65)(66)(67). No such localization domain is present in the BxpB sequence.…”
Section: Assembly Of the Exosporiummentioning
confidence: 99%
See 1 more Smart Citation
“…Study result previously showed that to obtain protein samples for immunoprecipitation, BclA-eGFP fusion-expressing sporulating cultures in Tiger broth at T 5 were harvested by centrifugation, and the cells lysed by bead-beating using 0.1 milli meter glass beads (Biospec Products). 28 Other studies show that there are similarities endospores surface antigen between Bacillus cereus and Bacillus anthracis. Result of analysis showe that anthrose is monosaccharide, who compiled tetrasaccharide on endospre of Bacillus anthracis.…”
Section: Discussionmentioning
confidence: 97%
“…Sporulation was essentially complete (>95%) after 72 hours. 28 Some spore proteins play roles in assembly of both the coat and exosporium. CotE of Bacillus anthracis directs assembly of at least one coat protein other than itself.…”
Section: Discussionmentioning
confidence: 99%